Division of the Lithuanian National Movement Into Periods - Vėbra, Rimantas (Problemos, 1968)
The analysis of literature shows that as to the problem of the division of the Lithuanian national movement into periods (as well as to the problem of its genesis) there exist quite different and even contradictory opinions and much confusion of a theoretical character. Holding one methodological principle (i.e., social-class principle) the author tries to distinguish qualitatively different periods and stages in the Lithuanian national movement.